# Algebra

Solve Q= (N-S)/ N for N

So when I multiply both sides by N
I get Q(N)= N-S
I know I am doing something wrong, the answer is in the book which is
N=S/(1-Q)but I don't understand were the 1 comes from. Could you write it out step by step, so I can see what I don't yet understand?

Here's one way to solve for N.

Q = (N - S)/N

Factor out N in the numerator:

Q = N(1 - S/N)/N

Cancel out N in both numerator and denominator to end up with this:

Q = 1 - S/N

Subtract 1 from both sides:

Q - 1 = - S/N

Multiply both sides by N:

N(Q - 1) = - S

Divide both sides by (Q - 1):

N = - S/(Q - 1)

Factor out -1 to end up with this:

N = S / (1 - Q)

I hope this will help.

thanks, I would have never gotten that far. I didn't know that the N could be factored out like that- to get 1, so with this knowledge I try other problems and see if it works out for me.

1. 👍 0
2. 👎 0
3. 👁 73

## Similar Questions

1. ### Algebra

Solve S=a/(1-r) for r S = a/(1-r) Multiply both sides by 1-r S*(1-r) = [(1-r)*a]/(1-r) Simplify S*(1-r) = a Multiply terms on the left. S - S*r = a Subtract S from both sides. S-S*r - S = a - S Simplify -S*r = a - S Multiply both

asked by Sara on July 19, 2007
2. ### Algebra

89. Solve for x in the equation: 6/7x - 6 = -2 I posted this before, and this is the reply I got from someone: multiply both sides by 7 6x-42=-14 add 42 to each side 6x=28 x=14/3 But I don't get how this is done because to

asked by y912f on May 7, 2010

Help to solve this 1/2 (3g-2) = g/6 nevermind I was missing a bracket in the solution. multiply both sides by 2 This gives 3g-2=g/3 now cross multiply to get 9g-6=g now add a -g to both sides and +6 to both sides. g=3/4

asked by Confused on October 24, 2006
4. ### Algebra

Solve each literal equations for the indicated variable D = C - s/n ( for s) s/n = D - C Next, multiply both sides of the above equation by n, to get the equation for s. i don't understand could you type it how it looks This is an

asked by Tammy Evert on July 8, 2006
5. ### math

x/2=3y/5 can you show me how you got the answer please y=3/4x-2 I don't think it is correct. Starting over To solve for y first multiply both sides by 5 (5)x/2=3y/5 (5) Cancel 5 on right side to get 5x/2=3y Now multiply both sides

asked by Angel on July 7, 2005
6. ### Math, rational inequalities

Please can someone help me solve this problem? 2/x + 6/x-1 less than or = -5 8/x -1 = -4x Divide both sides by 4 2 >= -x Multiply both sides by -1 -2

asked by agirl on November 26, 2006

x/3-2/3=1/x *Solve the rational below. I really need help. multiply both sides by x. x^2/3 -2x/3 = 1 multiply both sides by 3 subtract three from each side x^2 -2x -3=0 (x-3)(x+1)=0 Then either of the factors can be zero, or x=3

asked by margie on March 4, 2007
8. ### Maths

you have to solve the following by finding the value of x and y. can u help please? x+3(x+1)=2x 1+3(x-1)=4 2x-2(x+1)=5x 2(3x-1)=3(x-1) 4(y-1)+3(y+2)=5(y-4) 3y+7+3(y-1)=2(2y+6) These are exercises in standard algebraic manipulation

asked by number 420 on April 22, 2007
9. ### Algebra 2

-2/3x + 3

asked by Daren on January 22, 2007
10. ### Solving Equations with Rational Expressions

Can someone please show me how to solve these for me? 5/(y-2)=y+2 (x/3)-(2/3)=(1/y-5) (y+2)/7=1(y-5) (x^2)/(x-4)-7/(x-4)=0 x^2/(x+3)-5/(x+3)=0 I assume that your second equation has y as a typo. I will use that as an example.

asked by Mike on May 29, 2007

More Similar Questions